The 'Full Liberty of Public Writers': special treatment of institutional journalistic speech in English law - Danbury, R (2010)
This paper is an investigation into one aspect of the constitutionality of journalistic freedom in the law of England and Wales. It argues that there are instances where the law provides special treatment for the expression of institutional journalists, and that this is legitimate. The paper has two distinct parts, the doctrinal and the theoretical. Chapter one is doctrinal, and establishes that the law does provide special treatment to institutional journalistic speech. It classifies such treatment, demonstrating that these privileges come in different forms, and create different layers of rights. These forms can be distinguished according to whether the privileges are afforded to institutional journalists or functional journalism, or merely to general speech. The theoretical part of this paper forms chapters two and three. Chapter two assumes that the provision of special treatment to institutional journalists is justified where institutional journalistic speech particularly promotes free speech values. It argues that institutional journalistic speech does indeed perform such a function, by virtue of particular characteristics it possesses, namely reach and reputation, which are employed in processes such as reporting, investigating and interrogating. Chapter three considers the counter-arguments to this position. First it considers some arguments that challenge the thesis assumed in chapter two, and then it considers more specific criticisms of the provision of special treatment to institutional journalistic speech. It concludes that, while these limit the validity of the law’s affording special treatment to institutional journalistic speech, they do not extinguish it.